Suitability and assessment of the dams water for the purpose of agricultural irrigation - Aşık, Barış Bülent; kapdı, Esra Bozan (International Journal of Agricultural and Biological Engineering, 2024)
This study was carried out to evaluate the water quality of selected dam lakes as well as their suitability for agricultural irrigation. Seven dams were selected for water sampling and samples were collected monthly, including during the irrigation season for a period of one year from March to September 2019. The samples were analyzed for temperature, pH, physicochemical parameters such as temperature, pH value, salinity (EC), anions (CO3, HCO3, CI, SO4, P, NO3), cations (Na, K, Ca, Mg, B, NH4) and heavy metals. The irrigation suitability assessment was made using various indices such as SAR (sodium adsorption rate), TDS (total dissolved solids), Na% (sodium percentage), RSC (residual sodium bicarbonate), MAR (magnesium adsorption rate), KR (Kelly ratio), and PI (permeability index). The temperature values of the water samples varied between 5.8ºC-25.1ºC, pH and EC values changed between 7.51 and 8.46, 282, and 1400 µS/cm respectively. The water samples were evaluated as C2S1 and C3S1 irrigation water classes. The heavy metal contents of the water samples were determined below the limit values. Selected dams were found suitable for irrigation in terms of EC (salinity), SAR (sodium adsorption rate), TDS (total dissolved solids), Na% (sodium percentage), RSC (residual sodium bicarbonate), MAR (magnesium adsorption rate), and KR (Kelly ratio). Water samples were determined as the second class of PI (permeability index). Güllübağ dam was not found suitable as irrigation water in terms of EC, Na%, RSC, and KR values. As a result, it specifically points to the restrictions on the use of water from the Güllübağ dam for irrigation purposes. Keywords: anions, cations; irrigation water, water quality DOI: 10.25165/j.ijabe.20231606.7725 Citation: Aşık B B, Kapdı E B. Suitability and assessment of the dams water for the purpose of agricultural irrigation. Int J Agric & Biol Eng, 2023; 16(6): 255–262.